HUBUNGAN ANTARA PERLAKUAN ORANGTUA DENGAN PENERIMAAN DIRI SISWA - Hartati, Juli; Erlamsyah, Erlamsyah; Syahniar, Syahniar (Universitas Negeri Padang, 2013)
Parents greatly contribute to helping the child's personality, especially in the reception children. Guiding children to treat them well, so that self-acceptance to the child being good. Phenomena that occur in the field are still many parents who guide their children in the form of unfavorable treatment so that the child becomes low self-acceptance. The purpose of this study was to describe the treatment of parent and student self-acceptance and to see the relationship between parental treatment with self-acceptance. This research is a descriptive correlational, The research found that: good treatment of parents classified, categorized as either self-acceptance, there is a significant relationship between parental treatment with self-acceptance of students.